The november man ebook - Granger, Bill (November Man, 2014)
(Previously published as There Are No Spies .) SOON TO BE A MAJOR MOTION PICTURE STARRING PIERCE BROSNAN - IN THEATERS AUGUST 27TH! The classic thriller featuring the lethally cool U.S. government spy code-named The November Man The president learned long ago that the CIA could not be trusted. And so he created his own group of deadly efficient men to gather independent intelligence: a watchdog organization to keep the CIA in check. R Section was born. "There are no spies . . . " Until he heard those four simple words, Devereaux thought he'd left his days in R Section behind. He was no longer The November Man, an American field officer in the vice-grip of duty and danger—and the most brilliant agent R Section had ever produced. When he receives the cryptic message from Hanley, his former handler, Devereaux has no idea he's about to be reactivated into a mission to save both his life and R Section itself. He's not aware that a beautiful KGB agent has been ordered to stalk and kill him-or that Hanley is now in a government-subsidized asylum for people with too many secrets. And he doesn't know that zero hour ticks closer for an operation to catch a master spy . . . with Devereaux the designated pawn. What The November Man doesn't know can kill him.